2015
DOI: 10.1039/c5mb00262a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T68A/N126Y mutations on the conformational and ligand binding landscape of Coxsackievirus B3 3C protease

Abstract: 3C protease of Coxsackievirus B3 (CVB3) plays an essential role in the viral replication cycle, and therefore, emerged as an attractive therapeutic target for the treatment of human diseases caused by CVB3 infection. In this study, we report the first account of the molecular impact of the T68A/N126Y double mutant (Mutant(Bound)) using an integrated computational approach. Molecular dynamics simulation and post-dynamics binding free energy, principal component analysis (PCA), hydrogen bond occupancy, SASA, R(g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This virus belongs to the picornaviridae family and consists of a positive single-stranded RNA that exhibits frequent variation (Lum et al, 1998 ; Ho, 2000 ). Previous research on the relationship between viral genetic sequences and virulence mainly focused on two proteins: VP1 and 3D (Parks et al, 1989 ; Meng and Kwang, 2014 ; Zhang et al, 2014 ; Bhakat, 2015 ; Yuan et al, 2015 ). Some reports showed that a single mutation of VP1 or 3D would lead to great changes in the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This virus belongs to the picornaviridae family and consists of a positive single-stranded RNA that exhibits frequent variation (Lum et al, 1998 ; Ho, 2000 ). Previous research on the relationship between viral genetic sequences and virulence mainly focused on two proteins: VP1 and 3D (Parks et al, 1989 ; Meng and Kwang, 2014 ; Zhang et al, 2014 ; Bhakat, 2015 ; Yuan et al, 2015 ). Some reports showed that a single mutation of VP1 or 3D would lead to great changes in the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fluctuation in the Rg value of the mutated protease during the simulation period also indicates that, at some places, the structure became more rigid, while at other places it showed less compactness. Overall, the change in the Rg value of the mutated structure in comparison to the wild-type structure was in the line of mutation-based conformational distortion hypothesis, which ultimately results in a lose grip on the drug molecule [14].…”
Section: Effect Of the M46i Mutation On Conformational Compactnessmentioning
confidence: 65%
“…Molecular interaction studies are important for understanding the mechanism of biological regulation at the molecular level and as such also provides a theoretical basis for drug design and discovery [49,50]. Hydrogen and hydrophobic interactions are key players in stabilizing energetically favored ligands, in an open conformational environment of protein structures [29].…”
Section: Protein-ligand Interactionmentioning
confidence: 99%